PENGARUH EXPERIENTIAL MARKETING TERHADAP PEMBELIAN ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI (Survei pada Konsumen Wedangan di Mojosongo Surakarta) - Winda Kurniyawati, Marjam Desma Rahadhini & Edi Wibowo (Universitas Slamet Riyadi, 2018)
Aim of this research are to explain 1) influence of experiential marketing tocustomer satisfaction; 2) influence of customer satisfaction to repeat purchase; 3)explaining experiential marketing to repeat purchase and 4) explaining experientialmarketing to repeat purchase along customer satisfaction. This research is conducted atOmah Wedangan and Wedangan Konco Lawas Mojosongo Surakarta. Samplemeasurement is used as 165 respondents wih non-probability sampling technique andpurposive sampling method. Data analysis technique used is Structural EquationModelling analysis technique. Research result indicates indicates that there is influenceof direct experiential marketing towards customer satisfaction and repeat purchase;influence of direct customer satisfaction towards repeat purchase; and influence ofindirect experiential marketing towards repeat purchase along customer satisfaction.Based on aim of research, sugestion for the Wedangan to live in Mojosongo so thatupgrade customer satisfaction to pass experiential marketing until customer will gonetoo far to do repeat purchase way routine.Keywords: experiential marketing, customer satisfaction, repeat purchase